The Conflict Dynamics of General Election Commission of Republic of Indonesia and Ummat Party in 2024 - Mutiara, Pravita; Sembiring, Ruth Agnesia (Pusjar SKPP Lembaga Administrasi Negara, 2025)
This research discusses disputes in the 2024 General Election process involving Ummat Party, the General Election Commission of Republic of Indonesia (KPU), and Election Supervisory Agency of Republic of Indonesia (Bawaslu RI). This research also examines the dynamics of the conflict between the General Election Commission of Republic of Indonesia (KPU) and Ummat Party because of Decree of KPU number 528 of 2022 and the inconsistency of data and information. Ummat Party’s dissatisfaction led to fraud in its membership across two provinces. Tensions escalated as Ummat Party openly rejected the decision, only to end when it was declared eligible to contest the 2024 General Election. According to the research results, there was a miscommunication during the selection of political parties, and the dispute intensified due to fraud allegations. Therefore, to understand the reasons and effects of the administration of the 2024 General Election, the dynamics of this disagreement were analysed. This study finds that the fundamental causes of the dispute are data discrepancies, miscommunication, and a perceived lack of transparency during the factual verification. Nevertheless, the General Election Commission of the Republic of Indonesia (KPU) demonstrated its dedication to transparency and objectivity, adhering to electoral principles and existing regulations. This case highlights the vital significance of data accuracy and effective communication in preserving the integrity and public confidence in electoral processes. This qualitative research used interviews and documentation. The data analyses were performed using Conflict Theory, particularly the application of conflict wheel indicators. The informants were representatives of the General Election Commission of Republic of Indonesia (KPU) and the Election Supervisory Agency of the Republic of Indonesia (Bawaslu RI). At the same time, Ummat Party refused to be interviewed.